MISKONSEPSI PESERTA DIDIK PADA MATERI GEOMETRI SMP - Yahdi Yani (Jurnal Edukasi dan Penelitian Matematika, 2021)
Misconceptions exist in learning geometry at school. Therefore, this study aims to describe the forms of students' misconceptions in solving geometry problems. The research subjects were students of class VIII-1 and VIII-4 at SMP Negeri 5 Padang Panjang. The research instrument was in the form of essay questions and interview guidelines. The results of this study showed several misconceptions of students, namely: (1) misconceptions about the concept of height in a triangle; (2) error in determining the height of the pyramid; (3) errors in identifying prism elements such as base, cover, and height; (4) misconceptions about the concepts and formulas of the Pythagorean Theorem (5) errors in identifying and distinguishing geometric shapes based on their properties. The main cause of the misconception is the lack of knowledge construction process during the geometry learning process. This condition will result in students' shallow understanding of geometric concepts. Keywords - geometry and misconceptions